Évaluation de la contamination métallique d’une ressource en eau de la ville de Curitiba, Brésil - Didier Marie Jacques Joel Pitrat; Maria Cristina Borba Braga (VertigO)
Like many watercourses close to urbanized areas in Brazil, the Passauna River and its reservoir supplying the city of Curitiba suffers from organic pollution due to growing anthropogenic pressure. However, a recent study has detected a surprising enrichment of the sediments by Pb (> 100 ppm) and Cr (> 200 ppm), despite this basin’s protection against industrial pollution. The objective of this study was to assess the reality of this pollution and to understand the nature of the polluting sources. Measurements of trace metals were performed in water and sediments sampled in this basin, using trace-metal clean techniques and supplemented by grain-size and total organic carbon (TOC) analysis for sediments samples. The interpretation of the results has been supported by the calculation of contamination indexes (Enrichment Factor, Geo-accumulation Index) and the use of statistical analysis tools (correlation, PCA). This work showed that a former municipal landfill, located along the bank of the river, had a light and localized impact on the sediments with Cu, Pb and Zn. No impact with Pb has been recorded in the rest of the study area, but a geogenic source explaining the enrichment of superficial sediments with Cr has been detected in the lower part of the river and entrance of the reservoir.